hUCMSCs Mitigate LPS-Induced Trained Immunity in Ischemic Stroke - Feng, Yi-wei; Wu, Cheng; Liang, Feng-yin; Lin, Tuo; Li, Wan-qi; Jing, Ying-hua; Dai, Pei; Yu, Hui-xian; Lan, Yue; Pei, Zhong; Xu, Guang-qing (Frontiers in Immunology, 2020)
Innate immune memory is a part of the innate immune system that facilitates the elimination of pathogens. However, it may exacerbate neuropathology. In this study, we found that innate immune memory is detrimental in stroke, because it promotes the acute immune response and exacerbates ischemic infarcts. Mesenchymal stem cell therapy has been widely studied for its therapeutic potential in various diseases including stroke, but whether it diminishes innate immune memory has not been studied. Here, our study demonstrates that after the activation of innate immune memory by lipopolysaccharide, mesenchymal stem cell therapy can diminish innate immune memory though down-regulation of H3 methylation and subsequently protect against stroke. Our results demonstrate that innate immune memory is detrimental in stroke, and we describe a novel potential therapeutic target involving the use of mesenchymal stem cells to treat stroke patients.